Armenian kalāntars of the towns of Transcaucasiain the 17th-18th centuries - Kristine Kostikyan (Banber Arevelagitut'yan Instituti, 2023)
Kalāntars were the high officials of Şafavid, Afshārid and Qājār administration of towns, who managed the affairs referring to handicraft production and trade there. During the predominance of the Iranian states of the period the towns of Transcaucasia had kalāntars, and more often Armenian kalāntars were at the head of the towns, where Armenians formed the majority of the urban population. Armenian kalāntars were usually the representatives of local elite families of eminent melik‘s and merchants. The research on the topic has helped reveal the names of a few Armenian kalāntars in Agulis, Zagam, Loři, Erevan, Barda and Tiflis, also trace some peculiarities in the functions of this official in the region. The kalāntars of the mentioned towns usually managed the affairs of not only the town, but also those of the surrounding villages, since handicrafts and trade were among the main occupations of the inhabitants of many Armenian villages. The next peculiarity of office in the regions is the frequent cases of transmission of the post from father to son.